Coach decision-making in Futsal: from preparation to competition - Almeida, João (2019)
The purpose of this paper was to analyse expert futsal coaches process of decision-making from preparation to competitive moments. Ten expert and professional coaches’ (M = 46,9 ± 7,93 years old andM= 15,4 ± 7,22 years of coaching experience) from different countries were interviewed using asemi-structured interview (quantitative and qualitative) with two different goals: (1) evaluate the preparation for decision-making moment during the game; (2) classifying the importance of different game related points for decision-making during match moment. The data analysis was processed through combination of deductive and inductive methods through software QSR NVivo 11. The results revealed that coaches’ share similar ideas when preparing their teams. Coaches focus first their attention on their own team identity and frame andsecond on opposition team behaviour and frame. It was also possible to identify clear coaching behavioural signs possible to be structured as cues and guiding lines for their decision-making process and actions before and during competitive moments. Such information can be important for the development of most appropriated coaching education curriculums according to game demands specificities.